Las comisarías del Santo Oficio en la Audiencia de Filipinas. Conflictividad y comunicaciones en un espacio inquisitorial periférico, 1583-1784 - Miranda Ojeda, Pedro (Pontificia Universidad Católica del Perú, 2021)
The enormous geographical distances and slowness in communications between Mexico and the Philippines constituted a problem in the provision of trades. The Tribunal of the Holy Office of New Spain, on whom they depended on to carry out an effective inquisitorial activity, had to implement a series of actions with the aim of correcting all these inconveniences, Mexico’s inquisitorial court implemented a series of measures. The first was to grant a special concession to the Manila comisaria to be able to apply sentences in minor crimes. The second was to establish a territorial division of the diocesan comisarias to expand their presence to most of the populations of the islands. Finally, the simultaneous appointment of three comisarios who could replace the owner at any time in case of absence.

Las enormes distancias geográficas y la lentitud en las comunicaciones entre México y las Filipinas constituían un problema en la provisión de oficios. De ahí que, desde el siglo XVI hasta el siglo XVIII, hubo varios intentos por establecer un tribunal del Santo Oficio en Manila que al final no prosperaron. Con el objetivo de subsanar todos estos inconvenientes, el tribunal inquisitorial de México implementó una serie de medidas. La primera consistió en otorgar una concesión especial a la comisaría de Manila para poder aplicar sentencias en delitos menores. La segunda fue establecer una división territorial de las comisarías diocesanas con la finalidad de ampliar su presencia a la mayoría de las poblaciones de las islas. Por último, el nombramiento simultáneo de tres comisarios que pudieran sustituir en cualquier momento al propietario en caso de ausencia.
The Comisarias of the Holy Office in the Audience of Philippines. Conflict and Communications in a Peripheric Inquisitorial Space, 1583-1784
Keywords: Philippines; distances; communication; Holy Office; comisarias; Filipinas; Distancias; Comunicación; Santo Oficio; Comisarías; https://purl.org/pe-repo/ocde/ford#6.01.01